Comparison in haematological and biochemical changes in normal, acute and chronically castrated West African Dwarf goats - Olaifa, Abayomi Kayode (International Journal of Research in Medical Sciences, 2018)
Background: Castration is one of the frequent management practices in large animal husbandry and burdizzo castration has been shown to produce fewer long-term behavioral signs of pain and distress than banding. Castration is known to reduce virility and aggression due to the elimination of testicular androgens. Methods: This is a comparative study of hematological and biochemical parameters in intact, acute and chronically castrated West African dwarf goats. Twelve adult West African Dwarf bucks weighing between 8 to 14 kg randomly divided into 3 groups of intact, acute and chronic castrated. They were castrated using burdizzo castrator. Hematological and biochemical parameters were estimated by standard laboratory procedures. Results: There were significant decreases (P<0.05) in the PCV, Hb, RBC, WBC and MCH of acute and chronically castrated goat compared to the control group. The MCV and platelets increased significantly in acute and chronically castrated goat; while the neutrophil and lymphocyte showed no significant changes. The result also showed no significant changes in Na+, Cl-, K+, Ca2+, Cu2+, AST and Creatinine. Mg2+ and ALT significantly increased in chronically castrated goats compared with the acutely castrated goats while Zinc increased significantly (P<0.05) in acute castrated compared with the control goats. Conclusions: Therefore, from this study, either acute or chronic castration in goats have no detrimental effect on blood electrolytes, but mainly deter the hematopoietic process in the animal owing to testosterone and androgen depletion in castrate animals.